"Tu Teh Ro" - Fauza, Fauza Abdillah; Syeilendra (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2024)
This artwork aims to introduce to the wider community that Bacenang Art exists in Nagari Sinuruik, Talamau District, West Pasaman Regency. In the preparation of the work "Tu Teh Ro" is lifted from a pattern that exists in the art of bacenang, because this cenang is the core of an art. The author tries to apply the activities that existed at the time of bacenang art and mixed traditional art with a combination of modern instruments in the performance of the work. Tu Teh Ro's work is a complete work with a presentation of the development of the cenang rytem pattern which is worked in such a way that it is made into a new compositional form. This bacenang art is part of traditional arts that grow and develop in the Minangkabau community, especially in Sinuruik, Talamau District, West Pasaman Regency. The idea of developing rhythmic patterns that are developed into a form of new musical composition work that is mixed or collaborated with modern musical approaches. This artwork uses the method of improvising funk style music. By developing a rhythmic pattern and using improvisational methods, this approach will be worked into a form of musical composition with a new presentation.